ANTIOXIDANT PROPERTIES AND TOXICITY OF AQUEOUS EXTRACT AND COMMON MYRTLE SYRUP - E. Yu. Bakova; D. I. Pozdnyakov; D. A. Konovalov; N. N. Bakova; V. N. Orobinskaya (Современная наука и инновации, 2023)
The article presents the results of studying the antioxidant properties of water extract and common myrtle syrup. Aqueous extract and syrup of myrtle, being low-toxic substances, surpassed reference preparations according to experimental data.